Pemanfaatan Limbah Sampah Plastik sebagai Bahan Alternatif dalam Pembuatan Batu Bata Ramah Lingkungan - Susilawati Susilawati; Dinda Rizky Fadillah; Fanya Aurellya Putry; Nazwa Nazwa; Rezky Khabiza Syahdu (Pusat riset dan Inovasi Nasional, 2026)
Plastic waste is a form of solid waste originating from synthetic polymer materials that are difficult to decompose naturally and pose serious threats to environmental sustainability. Its accumulation continues to increase, causing pollution of soil, water, and ecosystems. In general, public attention is often limited to waste disposal and management activities without addressing preventive measures or innovative solutions at the source of the problem. This study aims to increase public awareness of plastic waste processing as an alternative approach to reducing the growing volume of plastic waste generated daily. One promising method explored in this research is the utilization of plastic waste as a raw material for producing environmentally friendly construction bricks. The study applied a simple descriptive experimental approach through direct practical activities, including the collection of plastic waste, processing and melting procedures, molding processes, and drying stages. The results demonstrate that plastic waste can be transformed into bricks with adequate physical strength and mechanical properties that comply with basic building standards. Therefore, this method has the potential to support sustainable waste management while providing alternative construction materials.